Case report: Implantation metastasis following stereotactic biopsy of pineal parenchymal tumor of intermediate differentiation in an adult patient: An exceptionally rare complication - Tandean, Steven; Siahaan, Andre Marolop Pangihutan; Loe, Michael Lumintang; Indharty, Rr Suzy; Julijamnasi; Sitorus, Mega Sari; Japardi, Iskandar; July, Julius (Frontiers in Neurology, 2022)
Implantation metastase after stereotactic biopsy in brain had been reported as another rare complications. A 36-years-old female was treated with VP shunt and stereotactic biopsy of a Pineal parenchymal tumor of intermediate differentiation (PPTID) with hydrocephalus. The patient underwent 5 cycles of radiotherapy on pineal area. Seven years later, patient developed left hemiparese with MRI brain showed enhancing mass along the biopsy tract. Craniotomy tumor removal was done with pathology consistent of PPTID. Focal on metastase area and craniospinal radiation was done. Patient was still disease-free in 2 years follow-up. The potential of implantation metastase following stereotactic biopsy of PPTID should be considered in the treatment plan and follow up. Expanding radiation area to cover entire biopsy tract may be beneficial option.